TEMPORARY PLASTIC CROWNS IN PROSTHODONTIC DENTISTRY: CLINICAL AND MATERIAL ASPECTS OF MODERN PROVISIONAL RESTORATIONS - Nabieva Sevda (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Temporary crowns are an essential component of fixed prosthodontic treatment, providing protection of prepared teeth, maintenance of occlusal function, and preservation of aesthetic appearance during the interim period before definitive prosthetic restoration. The present study analyzes clinical and material aspects of temporary plastic crowns, including their fabrication techniques, biomaterial properties, and associated complications. Special attention is given to acrylic and bis- acrylic resin systems, as well as CAD/CAM-based provisional materials. Clinical evaluation indicates that bis-acrylic materials demonstrate improved mechanical strength, superior marginal adaptation, and enhanced aesthetic outcomes compared to conventional acrylic resins. Proper fabrication protocols significantly reduce the incidence of complications such as gingival inflammation, crown dislodgement, and marginal leakage. The findings confirm the clinical importance of high-quality provisional restorations in achieving long-term success in fixed prosthodontic therapy.